Materiais híbridos Ureasil-polióxido de etileno/quitosana para aplicação na liberação controlada de fármacos - Paredes Zaldivar, Mayté [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work describes the synthesis and characterization of novel organic-inorganic hybrid materials, ureasil-polyethylene oxide (PEO)/chitosan, as controlled delivery system of drugs. Pramoxine hydrochloride was used as drug-model. It is a local anesthetic with widespread use in pharmaceutical preparations. Ureasil-polyether hybrids are biocompatible, flexible and transparent materials that have been used as controlled drug delivery systems, while chitosan is a biodegradable, biocompatible and low toxicity polymer, which has long been used for this same purpose. The synthesis was performed using the sol-gel method by adding chitosan to ureasil-PEO1900 hybrid precursor. Addition occurs during the acid hydrolysis and condensation reactions of this precursor. Hydrochloric and acetic acids were used as catalysts. Due to the insolubility of chitosan in ethanol and organic solvents, water was used in the hydrolysis solution as the main component or alone. The materials before and after drug addition were characterized by different physicochemical techniques such as FTIR (Fourier Transform Infrared Spectroscopy), DSC (Differential Scanning Calorimetry), TG (Thermogravimetric Analysis), XRD (X-Ray Diffraction), SAXS (Small Angle X-ray Scattering) and NMR (Nuclear Magnetic Resonance Spectroscopy). Studies of swelling and in vitro drug release in water were done. The last one study was done in different pH buffer solutions too. The kinetics of both processes was studied by the Ritger-Peppas model. The obtained materials were transparent, rubbery, flexible, water-insoluble, and showed low crystallinity. The chitosan and the drug showed a good dissolution in the hybrid matrix. This addition did not cause change in a natural tendency of PEO crystallization, did not affect the mobility of the chains or the inter-chain interactions of the amorphous polymeric phase. However, thermal stability of hybrids prepared with...

Este trabalho descreve a síntese e caracterização de novos materiais híbridos orgânico-inorgânicos, ureasil-polióxido de etileno (POE)/quitosana, para aplicação na liberação controlada de fármacos. Como fármaco-modelo foi utilizado o cloridrato de pramoxina, anestésico local que apresenta ampla utilização em preparações farmacêuticas. Os híbridos ureasil-poliéter são materiais biocompatíveis, transparentes e flexíveis que podem ser aplicados como sistemas de liberação controlada de fármacos, enquanto a quitosana é um polímero biodegradável, biocompatível e de baixa toxicidade que tem sido muito utilizado com este fim. A síntese foi realizada utilizando o método sol-gel através da adição da quitosana ao precursor híbrido ureasil-POE1900, durante a etapa de hidrólise ácida e condensação do precursor. Como catalisadores foram utilizados o ácido clorídrico e o ácido acético, e a solução de hidrólise teve a água como componente majoritário, ou único, para facilitar a adição da quitosana nestes materiais devido a sua insolubilidade em etanol e solventes orgânicos. Os materiais, antes e depois da adição do fármaco, foram caracterizados por diferentes técnicas físico-químicas como: FTIR (Espectroscopia de infravermelho), DSC (Calorimetria exploratória diferencial), TG (Analise termogravimétrica), DRX (Difração de raios X), SAXS (Espalhamento de raios X a baixo ângulo) e RMN (Espectroscopia de ressonância magnética nuclear). Ensaios de intumescimento em água e de liberação do fármaco, tanto em água quanto em soluções tampão com diferentes pH, foram realizados e suas cinéticas estudadas pelo modelo de Ritger-Peppas. Foram obtidos materiais transparentes, flexíveis, insolúveis em água e com baixa cristalinidade. Tanto a quitosana quanto o fármaco dissolvem-se na matriz híbrida, e a sua adição não causou modificação na tendência de...
Keywords: Processo sol-gel; Quitosana; Tecnologia de liberação controlada; Propriedades térmicas Propriedades termicas; Thermal properties